Study guide : HBEC 4103 Safety, health and nutrition in early childhood education - Badzis, Mastura (Open University Malaysai (OUM), 2013)
This course prepares students to develop understanding of their roles in promoting children's safety, health and nutrition as well as helping young children begin to establish good habits, attitudes and lifelong responsibility for optimisign personal well-being. students will also be exposed to a holistic approach and risk management for the safety, health and nutrition of young children.